Complex population genetic structure of the bark beetle predator Thanasimus formicarius (L.) (Coleoptera: Cleridae) across its European range - Papek, Eva; Derlic, Amina; Melin, Markus; Roques, Alain; Cocos, Dragos; Schroeder, Martin L.; Schebeck, Martin (Wiley, 2025)
Thanasimus formicarius (L.) (Coleoptera: Cleridae) is an important bark beetle predator and can reduce bark beetle population densities of some of the most severe forest pests in Europe. We analysed the population genetics and phylogeography of T. formicarius across its European range, using mitochondrial COI data from 187 individuals sampled from 23 locations. Our extensive sampling from the Fennoscandian to the Mediterranean region and from Iberia to the Middle East provides insights into the genetic structure of T. formicarius. We found a high genetic diversity, revealing 119 haplotypes across the sampling range. Two main clades, an Atlantic and a Continental, were identified, suggesting the presence of at least two glacial refugia during the last ice ages. An isolated population was discovered on the island of Corsica, suggesting that a limited number of individuals, probably from mainland France, may have colonized Corsica and a founder effect occurred. These findings increase our understanding of the recent evolutionary history of T. formicarius, which was shaped by Pleistocene events and certain species-specific life-history traits.
Keywords: ant beetle; Cleridae; COI; glacial refugia; natural enemy; phylogeography; Pleistocene; population genetics